ICG Fluorescence Technique for the Detection of Sentinel Lymph Nodes in Breast Cancer: Results of a Prospective Open-label Clinical Trial - Grischke, E.-M.; Röhm, C.; Hahn, M.; Helms, G.; Brucker, S.; Wallwiener, D. (Geburtshilfe und Frauenheilkunde, 2015)
Introduction: Detection of sentinel lymph nodes (SLN) is the standard procedure to evaluate axillary lymph node status in breast cancer. In addition to known and established procedures such as the blue dye method and scintigraphy, this study investigated the efficacy of a method based on use of the fluorescent dye indocyanine green (ICG). Patients and Method: A total of 126 women with breast cancer histologically verified by punch biopsy were studied during surgical removal of SLN. In addition to SLN marking with technetium and scintigraphy, intra-individual comparison was done using indocyanine green (ICG) for marking instead of the standard blue dye. Results: Scintigraphy had a detection rate of 96 %; the detection rate with ICG was just under 89 %. A body mass index (BMI) > 40 was found to be a limiting factor for the fluorescent method. Investigation into potential toxicities associated with the use of the fluorescent dye ICG revealed no systemic or even local side effects. The fluorescent method was found to be significantly less expensive than the scintigraphy method. Conclusion: The ICG fluorescence technique for the detection of SLN was found to be a valid and feasible method in clinical practice when compared directly with the blue dye method and scintigraphy.
Keywords: breast cancer; breast; gynecology; epidemiology